A Clinically Useful Anger Outcome Scale. (September 2021) - Levin-Aspenson, Holly Frances; Boyd, Simone Imani; Diehl, Joseph M.; Zimmerman, Mark
Abstract: In the present report from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project, we describe the development and validation of the Clinically Useful Anger Outcome Scale (CUANGOS). Current anger measures vary in their psychometric quality, clinical utility, and clinically relevant content coverage, and no one scale addresses all three of these key considerations. We aimed to develop a brief, clinically useful anger scale that (a) assesses clinically relevant aspects of anger, (b) performs well across different patient populations, and (c) is brief, accessible, and easy to use in routine clinical practice either as a stand-alone measure or as part of an assessment battery. Analyses included data from 2710 psychiatric outpatients and 1397 partial hospitalization patients. We used data from randomly drawn subsamples to select items with good psychometric properties and sufficient distinction from measurements of other emotional dysfunction, resulting in a 5-item scale. In reliability and validity analyses using the remaining participants, CUANGOS scores showed high internal consistency and appropriate test-retest reliability, as well as excellent discriminant validity from measurements of depression and anxiety. CUANGOS scores converged strongly with clinician ratings of subjective and overt anger and differentiated across all or almost all levels of clinician-rated anger severity. CUANGOS scores were also significantly higher in patients with anger-related disorders versus patients with other psychiatric disorders. Results provide promising evidence for the CUANGOS as a reliable and valid measurement of anger in clinical populations. Moreover, the CUANGOS is brief and feasible to incorporate into routine clinical practice.